POTENTIAL MOLECULES AGAINST COVID-19 FROM ANNONA MURICATA; AN IN-SILICO APPROACH - Miftahul Mushlih; Andika Aliviameita; Puspitasari Puspitasari; Ahmad Shobrun Jamil (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2022)
At the end of 2019, a new virus emerged from Wuhan, China named Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The key to viral infection to host cells is the use of the ACE2 receptor. This study aimed to explore the potential of drugs in Annona muricata plant using the Insilico method. Compounds obtained from KNApSAcK Based on the analysis using SwissADME (Lipinski creteria)criteria. 22 compounds passed the selection. Eight ligands were identified as being able to change the conformation of the initial form of RBD and ACE2 attachment. Eight molecules are able to change the initial conformation, namely Asimilobine, Coreximine, (+)-Stepharine, Coclaurine, Norcorydine, N- Nornuciferinhe, methoxyphenyl)methyl]-1,2,3,4-tetrahydroisoquinolin-5-ol, and Atherosperminine.